2004
DOI: 10.1523/jneurosci.2449-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Modulation Power and Phase Spectrum of Natural Sounds Enhance Neural Encoding Performed by Single Auditory Neurons

Abstract: We examined the neural encoding of synthetic and natural sounds by single neurons in the auditory system of male zebra finches by estimating the mutual information in the time-varying mean firing rate of the neuronal response. Using a novel parametric method for estimating mutual information with limited data, we tested the hypothesis that song and song-like synthetic sounds would be preferentially encoded relative to other complex, but non-song-like synthetic sounds. To test this hypothesis, we designed two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
135
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(144 citation statements)
references
References 47 publications
6
135
1
Order By: Relevance
“…Yet to our knowledge, only one previous study has examined neural discrimination of complex sounds based on the average cortical population activity in primary auditory cortex (Orduña et al 2005). In songbirds, previous studies at the cortical level have quantified information transmitted by single neurons (Hsu et al 2004;Wright et al 2002), discriminability between different categories of natural and synthetic sounds based on mean firing rates (Amin et al 2004;Grace et al 2003), and discriminability between different categories of natural sounds by ensembles of neurons (Woolley et al 2005). This is the first study to quantify the contribution of spike timing to the discrimination of complex sounds by single neurons at the cortical level and the time scales underlying such discrimination.…”
Section: Cortical Discrimination Of Complex Soundsmentioning
confidence: 94%
“…Yet to our knowledge, only one previous study has examined neural discrimination of complex sounds based on the average cortical population activity in primary auditory cortex (Orduña et al 2005). In songbirds, previous studies at the cortical level have quantified information transmitted by single neurons (Hsu et al 2004;Wright et al 2002), discriminability between different categories of natural and synthetic sounds based on mean firing rates (Amin et al 2004;Grace et al 2003), and discriminability between different categories of natural sounds by ensembles of neurons (Woolley et al 2005). This is the first study to quantify the contribution of spike timing to the discrimination of complex sounds by single neurons at the cortical level and the time scales underlying such discrimination.…”
Section: Cortical Discrimination Of Complex Soundsmentioning
confidence: 94%
“…They were subsequently filtered using a symmetric two-dimensional (2D) Gaussian window with an SD of 1.3 samples. Modulation spectra were then calculated by taking the 2D Fourier transform of the spectrogram, and computing its power (Singh et al, 2003;Hsu et al, 2004). The average frequency modulation was then calculated by averaging along the temporal axis of the modulation spectra, and the average temporal modulation was calculated by averaging along the frequency axis.…”
Section: Methodsmentioning
confidence: 99%
“…Although representations close to sensory receptors can be reasonably well characterized by models that assume the responses are linearly related to simple features of the stimuli (Kim and Young, 1994;Pillow et al, 2005), these models fail as early as the cochlear nucleus (Nelken et al, 1997) and the inferior colliculus (Escabi and Schreiner, 2002) in the auditory system. Many laboratories are investigating the special problems associated with natural stimuli and sensory systems (Theunissen et al, 2000;Vinje and Gallant, 2000;Hsu et al, 2004;Machens et al, 2004). An ecologically important class of natural stimuli for primates is their vocalizations Hauser, 1999, 2001;Seyfarth et al, 2005), and an extensive body of behavioral research has shown that primates, including rhesus macaques, discriminate among different calls (Dittus, 1984;Gouzoules et al, 1984;Cheney and Seyfarth, 1988;Gouzoules et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…These areas are likely to be modulated by experience and learning. Indeed, unit recordings show that neuronal responses are more selectively tuned to learned vocal sounds in NCM (20,21) and CM (43)(44)(45), whereas the primary auditory subregions L2a and L2b are responsive to sounds within the wider species-specific spectrotemporal range (24,46,47). Measurement of long-term response habituation in NCM, by both electrophysiology and the study of the song stimulation-induced up-regulation of ZENK, has suggested that this area might encode the long-lasting sensory memory of the TUT (31,40).…”
Section: Familiar Song Stimuli Show Selective Differential Topographymentioning
confidence: 99%